PENDAFTARAN MEREK MELALUI MEREK DAGANG DI DALAM HUKUM PERJANJIAN (Trademark Law Treaty) - Ramiati Ranti Parwari (Fakultas Hukum Universitas IBA Palembang, 2021)
With the increasing development in these various aspects, developed countries and developing countries will continue to run well. Considering the technology - technology and products created are the work of human intellectuals which are of course useful and have economic value, the term Intellectual Property Rights (HAKI) is born, which is the right to property that is born due to human intellectual abilities. The Trademark Law Treaty determines which marks are registered and the procedure for applying them in the Indonesian National Law. Seeing from the description above, the author is interested in elaborating on the discussion of the trademark registration procedure and the constraints regarding the mark in terms of the Trademark Law Treaty. The existence of a trademark registration procedure through the Trademark Law Treaty relating to applications and changes to trademark registration and the provisions of the Trademark Law Treaty (TLST) is an international treaty regarding trademark registration procedures in administrative procedures in relation to national applications and trademark protection. With the ratification of the Trademark Law Treaty, the legal consequence is the application of the trademark registration procedure according to the Trademark Law Treaty in Indonesian national law, which in essence can be registered for several classes in one application for trademark registration. Judging from its application, namely in terms of changes and renewals in marks, namely registration of marks according to the Trademark Law Treaty and Law Number 15 of 2001 is basically limited to a change in identity, namely the name and address of the applicant or his attorney.